Role of Anthropometric Indices in Prediction of Non-Alcoholic Fatty Liver Disease in Type 2 Diabetes Mellitus Patients - Upadhyaya, Dr. Anvisha; Shukla, Deepak; Patel, Swati (International Journal of Innovative Research in Medical Science, 2024)
Introduction: The growing global incidence of diabetes, obesity and metabolic syndrome presents substantial public health challenges and is now recognized as a contributing factor to various systemic diseases. Also diabetic individuals, in particular, face a heightened risk, emphasizing the gravity of the underlying health issue. Failure to promptly recognize NAFLD can present a formidable healthcare obstacle. Anthropometric indicators are signiﬁcant in understanding the intricate relationship between obesity, NAFLD, and diabetes in the Indian demography. Aim: Establishing connections between diverse anthropometric indices, such as BMI, WHR, WHtR and NAFLD, pinpointing which of the patients diagnosed with type 2 diabetes displayed the most signiﬁcant predictive eﬃcacy when considering these indicators. Material and Methods: Data from 132 diabetic patients was scrutinized, standard methodologies were employed for collecting anthropometric data, ultrasonography was utilized and routine pathological and biochemical investigations were conducted. Results: The study unveiled correlation between BMI, waist to hip ratio, waist to height ratio and NAFLD in individuals with type 2 diabetes diagnosis. Conclusion: Anthropometric indices such as BMI, waist to hip ratio and waist to height ratio can serve as eﬃcient methods for identifying NAFLD, followed by an early intervention to tackle obesity, and help in reducing their negative eﬀects on type 2 diabetes mellitus.